Exploring satisfaction and outcomes in rhinoplasty: experience from a tertiary care hospital in Kashmir valley, India - Bashir, Durfishan; Qadri, Mir Sajad; Rather, Rouf Hussain (International Journal of Research in Medical Sciences, 2023)
Background: Augmentation rhinoplasty is a popular yet challenging procedure that aims to improve both the nasal appearance and quality of life of patients. The purpose of this study was to examine the satisfaction and outcome after augmentation rhinoplasty at a tertiary care hospital in Kashmir valley. Methods: The study was conducted at a tertiary care hospital in Kashmir valley among patients who underwent the procedure using autologous cartilage grafts at the ENT department from October 2021 to December 2021. The sample size was 56. The patients age, gender, pre-operative findings, surgical techniques, post-operative outcomes, complications, and corrective interventions were recorded. The rhinoplasty outcome evaluation questionnaire was used to evaluate the patients' pre and post-operative status, with outcome assessed three months after surgery. Results: The present study included 56 patients which comprised of 39 (69.64%) males. The mean age of patients was 41±9.6 years. The indication for surgery was a mix of aesthetic and functional reasons in 56% subjects with 78% undergoing a primary surgery. The mean pre-operative score on the ROE questionnaire was 9.21±0.8 which improved to a mean score of 19.56±1.1 at three months after surgery. Overall 75% (42/56) patients reported a post operative ROE score of ≥80%. There was a significant improvement in all domains assessed by the ROE questionnaire, including appearance and function. Conclusions: Augmentation rhinoplasty can provide satisfactory aesthetic and functional outcomes for patients with nose deformities with consistent improvement across all domains related to aesthetics and functionality.